About high efficiency of two-rotor wind power unit Bidarrieus-2 - Yershina, A.K.; Yershin, Sh.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
The article discusses the design features of the wind turbine Bidarrieus-2 with an abnormally high wind power coefficient. The basic design of HBI-rotor of the turbine Bidarrieus-2 is shown. Due to the twin-rotor construction the wind turbine Bidarrieus-2 has much more efficient than all modern wind power devices. In calculating of the power the wind turbine rotational moment has been taken into account. The study results of wind energy that can be converted by the Bidarrieus-2 wind turbine are confirmed it’s uniqueness.
Keywords: wind turbine; Darrieus; Bidarrieus-2; HBI-rotor; wind power coefficient